E-033 Single Session, Single Pedicle Injections in the Treatment of Brain Arteriovenous Malformations. (14th July 2013) - Durst, C; Evans, A
Abstract : Background and Purpose: Cure rates using traditional open surgical techniques decrease and risks increase as arteriovenous malformations (AVMs) increase in size, develop deep venous drainage, or encroach upon areas of eloquence. Using a percutaneous transluminal approach, Onyx may be used to cure AVMs in a single treatment session offering an alternative to open surgery. Materials and Methods: Twelve patients underwent Onyx embolisation of an AVM using a novel technique, termed the plug then push, in which a well-formed plug is formed around the treatment catheter prior to injecting the Onyx. The plug mitigates the risk of backflow and catheter entrapment, thereby allowing the user to inject higher volumes of Onyx at higher injection rates. All patients were followed clinically throughout the immediate post-operative course. Requests were made to return for 2 month, 12 month, and 24 month follow up imaging. Results: Using the plug then push technique, it was possible to inject an average of 8.8 mL of Onyx into the AVM, significantly more than using traditional techniques (p=0.049). The faster injection rate and need for only a single treatment session reduced treatment time by over 50% (p < 0.001). Angiographic cures were achieved in 83% of patients. There were three complications related to the procedure. Two resulted in permanent morbidity and one resulted in temporary dysarthria. There was a 12% recurrence rate with 1 patient demonstrating a recurrence at 24 months after initially appearing cured in follow-up. Conclusion: The plug then push technique allows for a more rapid injection of contrast due to the formation of a well controlled plug prior to treatment, mitigating the risk for backflow of Onyx and entrapment of the catheter. As such, complete obliteration of an AVM can be expected in at least 83% of cases after a single session, resulting in an approximate 50% reduction in total procedural time. Long term results from this study and the literature suggests that 6–12 months of follow-up imaging may be insufficient to declare a permanent angiographic cure. We suggest that a "cure" should not be declared until at least the 2 year follow-up demonstrates no residual or recurrent AVM. Disclosures: C. Durst: None. A. Evans: 1; C; The For the Love of Molly Foundation.